Achieving health equity : from root causes to fair outcomes : interim statement (The Commission GenevaCH, 2007)
Sets out the Commission's vision and goals, the problems it seeks to ameliorate, and the intellectual foundation for a social determinants approach.
Keywords: ACCESS TO HEALTH CARE